2022
DOI: 10.1002/aenm.202203611
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Oxygen Reduction Reaction on Atomically Dispersed Fe Sites via Establishing Hydrogen Bonding with the Neighboring P Atoms

Abstract: Single atom catalysts (SACs) comprised of nitrogen‐coordinated transition metal (TM–N–C) moieties show encouraging performance towards the oxygen reduction reaction (ORR). Nevertheless, for the reactions involving multiple intermediates, single‐atom sites fail to satisfactorily optimize the adsorption of all intermediates. Here, a facile strategy is reported to construct Fe, P dual‐atom sites in multimodal porous carbon (Fe,P‐DAS@MPC), and its superiority in synergistically boosting ORR is demonstrated. Fe,P‐D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 74 publications
0
43
0
Order By: Relevance
“…It should be noted that the P 2p XPS spectrum (Figure S7d) demonstrates a significant amount of P–O in addition to the P–C species. Since P has strong oxygen affinity, , the FeN 3 P configuration would be present as FeN 3 PO (the inset of Figure e) upon exposure to air in the atmosphere. All of these results demonstrate that the FeN 4 moiety in FeNC was transformed into FeN 3 P and finally into FeN 3 PO configuration in FeNCP, which is clearly distinguished from PH 3 -adsorbed FeNC.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted that the P 2p XPS spectrum (Figure S7d) demonstrates a significant amount of P–O in addition to the P–C species. Since P has strong oxygen affinity, , the FeN 3 P configuration would be present as FeN 3 PO (the inset of Figure e) upon exposure to air in the atmosphere. All of these results demonstrate that the FeN 4 moiety in FeNC was transformed into FeN 3 P and finally into FeN 3 PO configuration in FeNCP, which is clearly distinguished from PH 3 -adsorbed FeNC.…”
Section: Resultsmentioning
confidence: 99%
“…Hetero-dopants are not only able to induce a change in the electronic structure of the carbon basal plane but also chemically modulate the active sites, affecting the adsorption energy with regard to the catalytic reaction intermediates. , In particular, the P element, which belongs to the nitrogen group in the periodic table, has similar chemical properties to N with the same number of valence electrons. Thus, P-doping is regarded to have a high potential to finely tune the oxygen adsorption energy of M–N 4 moieties through coordination environment engineering of the central metal. Nonetheless, only a few studies have explored P,N-coordinated Fe active moieties since the discovery of ORR-active Fe–P coordination. , In this regard, creating new active sites by P-doping into Fe–N–C and elucidating the role of P-dopants are of great importance in achieving NPGM-based ORR catalysis. Moreover, experimental in situ observations , and fundamental DFT studies , have recently suggested that reaction intermediates during the ORR need to be considered to implement more realistic active states of catalysts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Sb–SeNC also exhibits an apparently larger BET SSA (1738 m 2 g –1 ) than Sb–NC (1188 m 2 g –1 ) and Se–NC (1251 m 2 g –1 , Figure f), accompanying abundant micropores, mesopores, and macropores (Figures g and S8), which is attributed to the two-step pyrolysis of Sb–SeNC, while it is one-step pyrolysis for both Sb–NC and Se–NC. Two-step pyrolysis is beneficial for the formation of hierarchical porous structures that expose more active sites and facilitate mass transport in ORR. , The X-ray diffractions (XRDs) in Figure S9 also show that all three samples only present two broad peaks at around 25 and 44°, indicating the absence of Sb and Se nanoparticles (NPs) and their compounds. …”
Section: Resultsmentioning
confidence: 99%
“…In addition, Zong et al 123 constructed multimodal porous carbon with Fe, P dual-atom sites (Fe,P-DAS@MPC) by a two-step strategy. DFT calculations revealed that the excellent ORR performance of the Fe,P-DAS@MPC catalyst was attributed to the Fe, P dual atom sites in the FeN 3 –PC 2 N coordination structure, which synergistically improved the desorption ability of the *OH intermediate on the active site, thus enhancing the ORR kinetic process.…”
Section: Applicationsmentioning
confidence: 99%